2010
DOI: 10.4293/108680810x12924466007241
|View full text |Cite
|
Sign up to set email alerts
|

Routine Preoperative Typing and Screening: A Safeguard or a Misuse of Resources

Abstract: The probability of requiring blood products for cholecystectomy, hernia repair, and appendectomy is low. The authors, therefore, suggest the elimination of routine typing and screening before these procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…Ghirardo et al replicated these results in 3,424 patient undergoing moderate risk general surgery procedures and again found little evidence to support mandatory preoperative T&S in light of 0.32% overall RBC transfusion rate. 16 Finally, Dexter et al confirmed the threshold of 5% predicted individual transfusion risk as appropriate to trigger preoperative T&S. 17 Beyond institutional requirements another reason that T&S are oftentimes ordered is that surgeons tend to over-utilize laboratory testing, possibly for medico-legal reasons or in the case of vascular surgeons, due to habituation to high risk procedures. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghirardo et al replicated these results in 3,424 patient undergoing moderate risk general surgery procedures and again found little evidence to support mandatory preoperative T&S in light of 0.32% overall RBC transfusion rate. 16 Finally, Dexter et al confirmed the threshold of 5% predicted individual transfusion risk as appropriate to trigger preoperative T&S. 17 Beyond institutional requirements another reason that T&S are oftentimes ordered is that surgeons tend to over-utilize laboratory testing, possibly for medico-legal reasons or in the case of vascular surgeons, due to habituation to high risk procedures. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Rapid administration of O-negative blood acceptably addresses any hemodynamic instability in an emergency situation with evidence that no patient has died from a transfusion complication and the rate of seroconversion in Rh-negative patients is low. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Laboratory tests include white blood count which may be useful in evaluating the postoperative outcome, in particular in patients with complications such as infections, or to check the evolution of leukocytosis when surgery is performed for acute cholecystitis [352]. Since the risk of transfusions is 0.7% for laparoscopic cholecystectomy (slightly higher in case of ''open procedure"), even the routine preoperative evaluation of haemoglobin and haematocrit is not considered mandatory [352,353]. Platelets count, international normalized ratio and partial thromboplastin time are often screened and requested to evaluate coagulation factors in patients scheduled for surgery.…”
Section: Preoperative Investigationsmentioning
confidence: 99%
“…30 Recently, Katz et al evaluated preoperative testing, recommended that hospitals screen for unnecessary tests, and recommended further investigation whether the benchmarked value to compare providers can be the percentage of patients with at least one unnecessary test. 1 Tsai's and Polk's subsequent Letter to the Editor emphasized the need to reduce variability in preoperative testing among providers.…”
Section: Discussionmentioning
confidence: 99%